IMPROVING WEAR RESISTANCE BY ELECTROLYTE-PLASMA HARDENING OF CORROSION-RESISTANT STEEL OF THE TIP - Kombayev, Kuat; Kim, Alina; Sypainova, Gulden; Yelemanov, Daniyar (Journal of Applied Engineering Science, 2023)
The development of new fields in the oil and gas industry of Kazakhstan, the exploitation of fields with hard-to-recover reserves, and the exclusion of harmful environmental impacts require the study of new advanced technologies in the manufacture of valves. Hardening of the throttle tip in the factory from low-carbon corrosion steel is provided traditionally: carburizing in a solid carburetor, followed by hardening and normalization in an electric furnace. However, this process is accompanied by high heat losses, long time spent on heating and cooling the furnace to the required temperature, and high-energy consumption - power costs are 60-100 kW/h. The carbon penetration rate is low, and for depths of 1-1.5 mm, it becomes necessary to heat the workpiece in a carburetor for 8-10 hours at a certain temperature, followed by hardening and normalization. The technological process of traditional hardening by cementation, followed by hardening and normalization, is accompanied by the appearance of various defects. The most common defects include the formation of microcracks, warpage, scale, and peeling of the metal, as well as high labor intensity and energy intensity. A technology has been developed for hardening the tip on an electrolytic-plasma modification installation, which includes heating the part to 910-9600C and quenching in an electrolyte flow at 330-3600C, characterized in that the part is heated by electrolyte plasma, the temperature of which exceeds 6000 K. Analytically and experimentally it was determined that heating with electrolyte plasma for quenching is achieved within 4 seconds and quenching in the electrolyte flow is achieved within 8 seconds. With cyclic electrolytic plasma hardening at the 10th cycle with 40 seconds of total processing, optimal hardening rates are achieved. An electron microscopic study of the hardened structure indicates a phase transformation and the formation of hardening martensite with a carbide network, which strengthens the steel. The tribological properties and friction coefficient of the surface layers formed during electrolytic-plasma hardening indicate an increase in the wear intensity by more than two times.